(3MhGOK GdTGes - (3HQjc , ejNGFjd HQjc GdNhQj,J (B1306 (3g` s
(3ChdgG (B:s
(3GYde HCfi GfG GdabjQ cGJHg GdNhQi s
(3ahJhZQGa Yf CUd HdG JGQjNs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B337 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B57s
(3HQhcdeGf edMb (B- (3GdLRA (B3 - (3U (B423 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B119 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdJjehQjI (B((3JGQjN (B2406) s
Keywords: (3GdJGQjNs